Augmented reality in higher school as a tool for implementation of STEM education - Knysh, Inna; Palshkova, Iryna; Balalaieva, Olena; Kobernyk, Halyna; Tiahur, Vasyl (My University, 2024)
The article provides a meaningful definition of the concepts of STEM technology, STEM education, STEM approach, and STEM training; the meaning and main ways of using elements of augmented and virtual reality for higher education as a means of implementing STEM education are revealed. The purpose of the article is to show the importance and necessity of using elements of augmented reality in higher education as a means of implementing STEM education. As a result, an experimental study was conducted to clarify the state of development and the use of modern innovative technologies in education, clarifying the question – of to what extent modern technologies can effectively organize distance learning, and STEM education in higher education when using elements of augmented reality, which are provided to messengers preference of educators, which platforms are used by teachers in working with students of higher education during quarantine, etc. The conclusions summarize the most effective modern technologies for preparing and conducting practical online classes in higher education as a means of implementing STEM education and highlight the most important condition for creating a STEM environment in higher education.

У статті подано змістовне визначення понять STEM технології, STEM-освіта, STEM-підхід та STEM навчання; розкрито значення та основні способи використання елементів доповненої та віртуальної реальності для вищої школіи як засобу реалізації STEM-освіти. Мета статті – показати важливість і необхідність використання елементів доповненої реальності у вищій освіті як засобу впровадження STEM-освіти. У результаті проведене експериментальне дослідження з метою з’ясування стану розвитку та використання сучасних інноваційних технологій в освіті, з’ясування питання – наскільки сучасні технології можуть дозволити ефективно організувати дистанційне навчання, STEM-навчання у вищій школі при використанні елементів доповненої реальності, яким месенджерам надають перевагу освітяни, які платформи використовують викладачі у роботі із здобувачами вищої освіти під час карантину, тощо. У висновках узагальнено найдієвіші сучасні технології підготовки та проведення практичних онлайн-занять у вищій школі як засобу реалізації STEM-освіти та виокремлено найважливішу умову створення STEM-середовища у вищій школі.
Доповненa реальність у вищій школі як засіб реалізації STEM-освіти
Keywords: elements of augmented reality; higher school; STEM education; students of higher education; modern innovative technologies in education; елементи доповненої реальності; вища школа; STEM-освіта; здобувачі вищої освіти; сучасні інноваційні технології в освіті